(untitled) (ASEAN Engineering Journal, 2022)
The wind characteristics in Barangay Bagasbas Daet, Camarines Norte, by way of 5-year win data at a 10-m elevation was analyzed using the data gathered from PAGASA or the Philippine Atmospheric Geophysical and Astronomical Services Administration. The area has an overall mean wind speed of 3.36 m/s at 75 degrees North of East. By way of Weibull model to fit the wind data distribution recording an annual wind density of 52.94 W/m2. Power curves used for the estimate of the annual generated energy are 3 KW(V), 5 KW(V), 10 KW(V), 10 KW(H) and 20 KW(H) for small-scale turbine. A value of about 17,095.23 kWh/year was expected for the annual production of energy for 20 KW(H) wind turbine. However, the 5 kW(V) wind turbine shows the highest capacity factor of 13.97%.